Pesan Dakwah dalam Tradisi Panjang Jimat: Akulturasi Islam dan Budaya Lokal dalam Praktik Keagamaan Masyarakat - Nur Pratiwi, Putri; Shodiqin, Asep (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2014)
The purpose of this study is to know the procession and da’wah message of Panjang Jimat tradition. This research refers to cultural theory, cultural da’wah theory, syuubiyah waqobailiyah theory and Max Weber's theory of social actionis framework of thinking in which thetruth is empirical or social as a result of social construction, The paradigm of konstructivism with a qualitative descriptive study approach. The Observation, interview and dokumentation data collection tehniques. The results of the study were based on an analysis of the process of carrying out the long tradition of talismans consisting of a preparation session, a tradition implementation session and ended with a barzanji reading session. The message of da'wah in the long tradition of talismans consists of a message of creed, namely the meaning of siji kang diruwat or one that is guarded, namely creed and a message of morality, which is the meaning to follow all the behavior of the Prophet.